Analgesic Efficacy of Preemptive Transversus Abdominis Plane Block in Patients Undergoing Laparoscopic Colorectal Cancer Surgery - Kwan Young Hong (Journal of Clinical Medicine, 2020)
Despite rapid advancements in laparoscopic surgical devices and techniques, pain remains a significant issue. We examined the efficacy of preemptive transversus abdominis plane (TAP) block for acute postoperative pain in patients undergoing laparoscopic colorectal cancer surgery. We retrospectively analyzed 153 patients who underwent laparoscopic colorectal cancer surgery with or without TAP block; among them, 142 were allocated to the TAP or non-TAP group. We performed between-group comparisons of demographic, clinical, and anesthetic data and pain scores at a postoperative anesthesia care unit (PACU) and at postoperative days 1, 3, and 5. There were no significant between-group differences in demographic and clinical characteristics. The mean arterial pressure, heart rate, and minimum alveolar concentration (MAC) were significantly lower in the TAP group at the start and end of surgery. The post-extubation bispectral index was significantly higher in the TAP group. There were no significant between-group differences in the pain scores and opioid consumption at the PACU or at postoperative days 1, 3, and 5, or in the time to pass flatus, the hospital stay length, and postoperative complications. Preemptive TAP block showed an intraoperative, but not postoperative, analgesic effect, characterized by a low mean arterial pressure, heart rate, and MAC.